The Supreme Court in the early republic : the chief justiceships of John Jay and Oliver Ellsworth - Casto, William R., 1946- (Chief justiceships of the United States Supreme Court., 2012)
An insightful look at the first Supreme Court and the controversies that surrounded the judicial body.